2022
DOI: 10.1016/j.cresp.2022.100039
|View full text |Cite
|
Sign up to set email alerts
|

Be Good to Your Mother (Earth): The Relationship between Anthropomorphising Nature, Financial Insecurity, and Support for Pro-environmental Policies in the Context of the Coronavirus Pandemic

Abstract: Anthropomorphism of nature is known to be related to pro-environmental outcomes; however, little is known about these variables in the context of the coronavirus pandemic. The economic impact of the prolonged lockdowns may disrupt the historical relationship between these variables, as financial insecurity may compete with environmental concerns for consideration. This study examined the relationship between anthropomorphism of nature the context of COVID-19, and pro-environmental support, and the potential mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…According to the PLS-SEM results, NAMF had a positive effect on environmental empathy and pro-environmental behavior. These results are in line with previous research (Tam et al, 2013 ; Chang and Wu, 2015 ; Moon et al, 2016 ; Amatulli et al, 2019 ; Liu et al, 2019 ; Tam, 2019 ; Karpinska-Krakowiak et al, 2020 ; Williams et al, 2021a ; Borovik and Pensini, 2022 ). When anthropomorphism is coupled with negative information, empathy is triggered (Slovic, 2010 ) and researchers have found that when negative information is paired with anthropomorphic cues, they are more effective in inspiring green intentions (Karpinska-Krakowiak et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the PLS-SEM results, NAMF had a positive effect on environmental empathy and pro-environmental behavior. These results are in line with previous research (Tam et al, 2013 ; Chang and Wu, 2015 ; Moon et al, 2016 ; Amatulli et al, 2019 ; Liu et al, 2019 ; Tam, 2019 ; Karpinska-Krakowiak et al, 2020 ; Williams et al, 2021a ; Borovik and Pensini, 2022 ). When anthropomorphism is coupled with negative information, empathy is triggered (Slovic, 2010 ) and researchers have found that when negative information is paired with anthropomorphic cues, they are more effective in inspiring green intentions (Karpinska-Krakowiak et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Anthropomorphism has a positive effect on customer preferences, engagement, and purchase intentions (Kim et al, 2016 ; Schroll et al, 2018 ). A study of anthropomorphism and its relationship to nature demonstrated a link between anthropomorphism and environmental concerns (Borovik and Pensini, 2022 ). Minimizing social distance and fostering social connections is critical for assisting people in engaging in pro-environmental behaviors (Schultz, 2002 ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Having directly observed the benefits of a pause to environmentally detrimental activities, it is likely that the public may be supportive of policies and ways of living that can lead to similar outcomes post-pandemic. For instance, in Australia, COVID-19-related anthropomorphism (ascribing human characteristics to non-human entities) was predictive of support for pro-environmental pandemic recovery policies and travel restrictions ( Borovik & Pensini, 2022 ; Pensini & McMullen, 2022 ). In Borovik and Pensini's (2022) study, support was unexpectedly stronger among those experiencing financial insecurity during the pandemic – suggesting a shift in how people typically prioritise their needs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Australia, COVID-19-related anthropomorphism (ascribing human characteristics to non-human entities) was predictive of support for pro-environmental pandemic recovery policies and travel restrictions ( Borovik & Pensini, 2022 ; Pensini & McMullen, 2022 ). In Borovik and Pensini's (2022) study, support was unexpectedly stronger among those experiencing financial insecurity during the pandemic – suggesting a shift in how people typically prioritise their needs. Hence, rather than solely focusing on economic recoveries, “policymakers should acknowledge and attempt to preserve societal changes which have simultaneously benefited human wellbeing and biodiversity” ( Cooke et al, 2021, p. 113 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scores were summed, after recoding one reverse-scored item. An example item includes “Nature is sending us a message with the COVID-19 pandemic.” These items have been used previously (e.g., Borovik & Pensini, 2022; Pensini & McMullen, 2022), where they have demonstrated good internal consistency reliability (α = .87–.88). Similarly, in the current study, α = .90.…”
Section: Methodsmentioning
confidence: 99%